How Much Does A Company's Reputation Matter in Recruiting? - Alniacik, Esra; Gardberg, Naomi; Devinney, Tim; Korschun, Daniel; Windsperger, Josef; Eroglu, Sevgin; Hult, G.; Lawrence, Benjamin; Brickley, James; Shaw, Kathryn; Spell, Chester; Groysberg, Boris; et al. (MIT Sloan Management Review, 2013)
Recently, the idea has emerged that a key to winning the talent war through recruitment is to place greater emphasis on an organization's reputation for social responsibility, not just the company's overall reputation or its reputation as a good employer. But, the authors argue, few studies validly examine the degree to which a company's social reputation or other aspects of its reputation are more or less important than other, more utilitarian job choice factors. When a survey task simply asks people to rate the importance of a laundry list of job attributes such as corporate social responsibility, it hides the marginal value of each attribute to the potential employee. The authors report on three job choice studies they undertook -- one with a sample of MBA students, the second with white-collar office workers and the third with workers from a mixture of occupations (legal, medical, government/public service and manual labor). They systematically analyzed the way potential and actual employees make choices involving job contracts with various utilitarian and reputation components. From the results of their research, the authors conclude that for potential employers of MBA students, neither a corporate reputation for social responsibility nor a reputation as a good place to work is as important as those facets of the job contract that are more directly material to MBAs' careers -- salary, compensation structure, time demands and promotion opportunities. These talented employees want to work for good employers, the authors conclude, but their employers do not have to be leaders in corporate social responsibility. Across job categories, the authors found a degree of heterogeneity that implies that overly simplistic prescriptions that do not account for the demands of workers in different professions could lead managers astray. For example, manual workers appear to be less concerned about a company's reputation, while those in the legal profession are clearly paying attention to the social and workplace dimensions of an organization's reputation. When it comes to reputation and the war for talent, the authors conclude, there is every indication it is not a case of one size fits all.
Keywords: Industrial management; Gestion d'entreprise